2022
DOI: 10.1101/2022.02.08.479600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza A virus reassortment in mammals gives rise to genetically distinct within-host sub-populations

Abstract: Influenza A virus (IAV) genetic exchange through reassortment has the potential to accelerate viral evolution and has played a critical role in the generation of multiple pandemic strains. For reassortment to occur, distinct viruses must co-infect the same cell. The spatio-temporal dynamics of viral dissemination within an infected host therefore define opportunity for reassortment. Here, we used wild type and synonymously barcoded variant viruses of a pandemic H1N1 strain to examine the within-host viral dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…However, the effect of the bottle neck may vary, depending on species and transmission route ( 45 ). In avian hosts, the replication and dissemination of progeny AIV occurs via both the respiratory and enteric tracts, suggesting that two anatomically separate bottle necks may function simultaneously in infected birds as has been hypothesized previously ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 62%
“…However, the effect of the bottle neck may vary, depending on species and transmission route ( 45 ). In avian hosts, the replication and dissemination of progeny AIV occurs via both the respiratory and enteric tracts, suggesting that two anatomically separate bottle necks may function simultaneously in infected birds as has been hypothesized previously ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 62%
“…In addition, cellular coinfection can augment viral yield from productively infected cells by increasing the efficiency of core viral processes (17). Localized viral spread yields areas of high MOI, providing ample opportunity for coinfection, complementation and enhanced replication (15,21). At the within-host scale, our data reveal a competitive effect wherein the virus introduced at a higher dose or an earlier time point suppresses the replication of the other.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, cellular coinfection can augment viral yield from productively infected cells by increasing the efficiency of core viral processes (17). Localized viral spread yields areas of high MOI, providing ample opportunity for coinfection, complementation and enhanced replication (15, 21).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that all transmission pairs had equal bottlenecks even when we tested mutually exclusive transmission pairs. Second, virus populations may be spatially segregated within hosts, and the transmitted population may not have been well sampled by our analysis of nasal swabs (49)(50)(51)(52)(53). However, given the low viral diversity identified in nearly all cases, even spatially segregated viral populations are likely to be genetically similar to each other.…”
Section: Discussionmentioning
confidence: 98%